Comparison of apparent diffusion coefficients (ADC) and distributed diffusion coefficients (DDC) in high-grade gliomas - Kwee, Thomas C. (2010)
PURPOSE: To compare apparent diffusion coefficients (ADCs) with distributed diffusion coefficients (DDCs) in high-grade gliomas. MATERIALS AND METHODS: Twenty patients with high-grade gliomas prospectively underwent diffusion-weighted magnetic resonance imaging. Traditional ADC maps were created using b-values of 0 and 1000 s/mm(2). In addition, DDC maps were created by applying the stretched-exponential model using b-values of 0, 1000, 2000, and 4000 s/mm(2). Whole-tumor ADCs and DDCs (in 10(-3) mm(2)/s) were measured and analyzed with a paired t test, Pearson's correlation coefficient, and the Bland-Altman method. RESULTS: Tumor ADCs (1.14 ± 0.26) were significantly lower (P = 0.0001) than DDCs (1.64 ± 0.71). Tumor ADCs and DDCs were strongly correlated (R = 0.9716; P < 0.0001), but mean bias ± limits of agreement between tumor ADCs and DDCs was -0.50 ± 0.90. There was a clear trend toward greater discordance between ADC and DDC at high ADC values. CONCLUSION: Under the assumption that the stretched-exponential model provides a more accurate estimate of the average diffusion rate than the mono-exponential model, our results suggest that for a little diffusion attenuation the mono-exponential fit works rather well for quantifying diffusion in high-grade gliomas, whereas it works less well for a greater degree of diffusion attenuation.